MORFOLOGI CERITA RAKYAT MALIND ANIM KANUME - Esther Rita Embram (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Yenam Kepala Perang Kanum is the folklore of Malind Anim Kanume, the tribe whose lived in the border zone of Sota Merauke Papua. This research is an effort to document oral literature and to analyze the morphology of Malind Anim Kanume  folklore based on Vladimir Propp’s theory. From the analysis, it is known that the folklore were consisted of eleven functions and four spheres of action.The value of this paper are about how to keep the promises and how to work for piece. The important think about the Malind Anim Kanume Sota culture preservation.